Social participation of people affected by leprosy after discontinuation of multidrug therapy - Nardi, Susilene Maria Tonelli; Paschoal, Vânia Del’arco; Zanetta, Dirce Maria Trevisan (Leprosy review, 2011)
To evaluate social participation of individuals completing treatment for leprosy and to describe the relationship with physical sequelae and sociodemographic characteristics. A cross-sectional, descriptive study was performed involving all leprosy affected people who were treated between 1998 and 2006 in São José do Rio Preto, Brazil. General and clinical data were collected and the subjects were assessed using the degree of physical disability of the WHO (DPD-WHO), the Eye-hand-foot (EHF) score, and the participation scale (PS), which measures social participation of individuals with stigmatising problems. Of the 335 people treated in the period, 223 (66.6%) were interviewed. Of these, 51.6% were women, the mean age was 54 years (+/- 15.7 years), 66.4% had up to 6 years of formal education, 42.6% worked and 26.9% were retired. There was a predominance of dimorphous (borderline) leprosy (39.9%). Participants' physical and mental health was considered good in the month preceding the interview in 50.2% and 59.2%, respectively. Disabilities according to the DPD-WHO and EHF scores affected 32% of the participants and restrictions in social participation occurred in 35.4%. Multivariate analysis demonstrated a significant association between restrictions in social participation and family income of less than three minimum salaries (US$ 160.50), associated diseases, hospitalisation within the previous year and physical disability. The prevalence of restrictions in social participation is high, even after completing treatment for leprosy. Physical disability, associated diseases, recent hospitalisation and low family incomes influence the social participation of these individuals.